SARANAKOHESI DALAM CERPEN â€œROBOHNYA SURAU KAMIâ€ KARYA A. A. NAVIS - MAYORE, TENRI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research entitled â€œCohesive Feature in short story â€˜RobohnyaSurau kamiâ€™ by A.A. Navisâ€. Discourse analysis is used in this research. The aim of this research is to describe and verbal grammar cohesive feature that emerge in the short story. This research is expected to help students or readers in understanding the using cohesive feature in short story. In this research, the writer uses Tariganâ€™sÂ  theoryÂ  (1987). The data have been collectedÂ  from the sentences which contain lexical and grammatical features of the short story. The method that use in this research is descriptive through content analysis. The result shows that there are many cohesive feature use in that short story. The most lexical cohesive feature used was Repetition, Synonym, antonym, Collocation, andÂ  Equivalency.Â  While the grammatical cohesive feature are pronominal, substitution, ellipse, and conjunction. Â  Keywords: Lexical and grammatical features, descriptive, short story â€˜RobohnyaSurauKamiâ€™Â  by A.A. Navisâ€